Biochemical response of Ocimum basilicum L. inoculated with Rhizophagus fasciculatus as a NaCl-stress mitigator - Agüero-Fernández, Yuneisy; Murillo-Amador, Bernardo; Mazón-Suástegui, José; Nieto-Garibay, Alejandra; Ojeda-Silvera, Carlos; Batista-Sánchez, Daulemys (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
Basil (Ocimum basilicum L.) is a medicinal and aromatic plant of commercial interest; it can be grown in salinized soils by applying a stress mitigator. The objective was to evaluate the biochemical response of two basil varieties inoculated with AMF Rhizophagus fasciculatus and appraise its usefulness as a NaCl-stress mitigator. A completely randomized design with a factorial arrangement, four replicates per treatment and four plants per replicate was used. Three factors were considered, (1) two basil varieties (Napoletano and Nufar); (2) three NaCl concentrations (0, 50 and 100 mM); and (3) R. fasciculatus inoculum absence or presence (0 and 10 g). The variables evaluated were a substrate chemical analysis; shoot (STP) and root (RTP) total protein content; shoot (SP) and root (RP) proline content; shoot (SGA) and root (RGA) glutathione peroxidase activity; spore count and colonization. The spore content was 50 to 70 spores per gram of inoculum. The STP and RTP were highest in both varieties in 0 mM with AMF and decreased in Napoletano in 100 mM. The SP and RP were highest in Nufar in 50 and 100 mM with AMF and lowest in Napoletano in 0 and 50 with AMF. The SGA and RGA were highest in Napoletano in 50 and 100 mM with AMF. The colonization was high; however, decreased as NaCl increased. These results suggest that inoculation with AMF has a positive effect to mitigate NaCl-stress and a biochemical benefit for basil plants.